PENGARUH FEE AUDIT, AUDIT TENURE DAN DUE PROFESSIONAL CARE TERHADAP KUALITAS HASIL AUDIT - Giovanny Bangun Kristianto (Jurakunman (Jurnal Akuntansi dan Manajemen), 2022)
The preparation of a financial report is an obligation for an industry both on a small, medium and large scale. Then another obligation is an assessment of the fairness of a financial report, where the assessment is carried out by an external party, namely the Public Accounting Firm (KAP). KAP as an external party or third party is employed by a company and becomes a liaison between the agent and the principal. Therefore, with this situation, there is an agency theory, which will cause agency costs for a company that uses its services. In providing an audit service in financial statements, an auditor who works at KAP needs to provide the best quality for the implementation of the audit carried out. This study presents factors such as audit fees, audit tenure and professional dues that will have an influence on audit quality. This research was conducted by distributing questionnaires to auditors at KAP in Java. Based on the results of research conducted, it is stated that the audit fee variable has no effect on the quality of the audit produced by the auditor, in other words, the audit fee given cannot predict the audit result that will be given. The second hypothesis states that the number of auditor engagements with clients (audit tenure) has a significant negative effect on the quality of the audit produced by the auditor. This means that the longer the audit time between the client and the auditor, for example more than three years, it will have a negative impact on the quality of the resulting audit due to weak independence. The third hypothesis gives the result that Due Professional Care has a significant and positive effect on audit quality, which means that the prudential principle of an auditor in obtaining evidence will provide better audit quality.